Nutrí-Colada - Chasiloa Chimbo, Nataly Angélica (2017)
The present research project had the objective of elaboration of the nutrí-colada de melloco (Ullucus tuberosus) of two varieties quillu and pucca with the percentage of soybean meal (Glycine max) a different formulations to give a new alternative of consumption and value added to the tuber since within the food industry currently seeks to innovate new processes using native raw materials of the country, solving the problem of low sowing of the varieties mentioned. The process of obtaining the flour was initiated with the reception and control of melloco quillu and pucca, heavy, washing and disinfection, cut, dehydrated 50 ° C for 18 hours, crushed, sieved, packed and sealed. It was subjected to physical and microbiological physical analysis, obtaining as a result the variability between the two varieties of the analyzed parameters, but that are suitable for the elaboration of the product the same ones that have been formulated with the flour of soybean and rest of complementary ingredients obtaining a powder mixture with an amount of 100 g of nutrí-colada. In addition, the best treatment of processed formulations was identified by sensory analysis evaluating their organoleptic characteristics such as color, flavor, odor, consistency and acceptability of the nutrí-colada, obtaining as a result the best t5 treatment which contains pucca flour + 21 % soybean, identified by tabulation of data in Excel and infoStad statistical programs. Finally the best t5 treatment was submitted to the physic-chemical and microbiological analyzes which is within the parameters established in the norm INEN 2602 and 2009, also nutritional in 100 g of nutrí-colada contains; protein 12 g, energy 376kcal and total carbohydrates 70 g, the retail price of 100 gr of nutrí-colada is $ 1.13 being an accessible price aporting with a new product rich in protein suitable for the consumption of people.